Prognosis of super-elderly healthy Japanese patients after pacemaker implantation for bradycardia. Issue 1 (July 2017) - Yamaguchi, Tetsuo; Miyamoto, Takamichi; Iwai, Takamasa; Yamaguchi, Junji; Hijikata, Sadahiro; Miyazaki, Ryoichi; Miwa, Naoyuki; Sekigawa, Masahiro; Hara, Nobuhiro; Nagata, Yasutoshi; Nozato, Toshihiro; Yamauchi, Yasuteru; et al.
Abstract: Background: The prognosis of super-elderly patients (age ≥ 85 years) who undergo bradycardia pacemaker (PM) implantation remains unknown. Methods: We retrospectively enrolled 868 patients (men 49.0%, 76.6 ± 10.6 years) who could walk unassisted and whose expected life expectancy was more than 1 year, receiving their first bradycardia PM implantation between January 1, 2006, and June 30, 2013. Clinical outcomes were compared between super-elderly patients ( n  = 201, mean age 88.6 ± 3.2 years) and younger patients ( n  = 667, 73.0 ± 9.3 years). Results: At the end of a median 1285-day follow-up, 128 patients (14.7%) died, of which 54 were cardiac deaths (42.2%). Mortality rates were similar between the groups (16.4% vs. 14.2%, log-rank p  = 0.56) and across different indications for implantation (atrio-ventricular conduction disturbance or sick sinus syndrome, p  = 0.59), initial rhythms (sinus rhythm or persistent atrial fibrillation, p  = 0.62), pacing modes (dual chamber pacing or VVI pacing, p  = 0.26), and ventricular lead positions (septum or apex, p  = 0.52). On Cox proportional hazard model analysis, hypertension [hazard ratio (HR) = 1.74, 95% confidence interval (CI) = 1.19–2.54, p  = 0.004], diabetes mellitus (HR = 2.18, 95% CI = 1.51–3.14, p  < 0.001), history of myocardial infarction (HR = 3.59, 95% CI = 2.49–5.16, p  < 0.001), and history of stroke (HR = 2.26, 95% CI = 1.51–3.37, p  < 0.001) were independent predictors for mortality. Conclusions: The mortality rate of super-elderly patients who had no critical illnesses and were healthy enough to walk unassisted at the time of PM implantation was not inferior to that of younger patients. Prognosis was determined by comorbidities, but not by age, PM indication, initial rhythm, pacing leads, or mode.